HUBUNGAN ANTARA KELINCAHAN DAN KOORDINASI MATA KAKI TERHADAP KETERAMPILAN DRIBBLING PADA TIM SEPAK BOLA MADRASAH ALIYAH NEGERI 4 MUARA FAJAR - Asman, M. Rifky Mappesameng; Vai, Aref; Mandan, Ali (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: The problem in this study is that there are shortcomings and weaknesses of the basic technical factors in MAN 4 Muara Fajar football players, namely sloppy dribbling during matches, so that it is not clear in which direction the ball should dribble. The aim of this study was to prove the relationship between dexterity of eye and foot coordination and dribbling ability. The population in this study was the MAN 4 Muara Fajar football team using a total sampling technique with a total of 16 students. This type of research uses an instrumented correlation approach, namely the Dribbling test, data analysis techniques for the Varian's test and the Linearity test. Based on the results of the study described by the authors in the previous chapter, the following conclusions can be drawn: There is a joint relationship between agility and ankle coordination on dribbling ability in the MAN 4 Muara Fajar Sepak bola team, where rtab has a significant level α (0 .05) = 0.514, meaning Rcount (0.901) > rtab (0.514). Key Words: Agility And Ankle Coordination, Dribbling, Football